Vowel harmony in Akan a consideration of Stewarts word structure conditions - George N. Clements (LibraryPress@UF, 1984)
Stewart [1983] presents a new framework for the analysis of Akan vowel harmony in which Word Structure Conditions (WSCs) are introduced to account for word-level phonotactic regularities. It is shown here that the WSCs, rather than simplifying the analysis of Akan, impose unnecessary complexity on it, requiring us to restate the unitary process of vowel harmony as a number of formally unrelated rules. It is concluded that with one further modification, the analysis of Clements [1981] can be maintained.